ARENA OF PUBLIC DOMINANCE SEEING THE TRANSFORMATION OF THE SOCIAL FUNCTION OF ISLAMIC ART JEDORAN TULUNGAGUNG - Winanti, Risa; Afiyanto, Hendra (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to analyze the existence and sustainability of Jedoran art in Tulungagung, a city in East Java. Jedoran art was brought to Tulungagung by Sunan Kalijaga in the 16th century and has a long history. However, a big question arises: Does Jedoran art currently have the same social function as when it first appeared, or is this the result of adaptation of the old Jedoran art to fit in with new cultures and traditions? This research was conducted in Tulungagung because it is a Mataram Islam territory with a relationship to the Yogyakarta Sultanate. The researcher used historical and ethnographic methods as well as Foucault discourse analysis to understand how Jedoran art has developed according to the discourse that appears in every era. The results show that the sustainability of Jedoran art is not separated from the ability of Jedoran artists to read and adapt to the discourse that develops in accordance with changes in time. In addition, this adaptation is actualized through the transformation of the social function of Jedoran art according to the discourse that appears in every era.